The use and relevance of the university library on the basis of attitudes and practices of early career researchers - Rodríguez-Bravo, Blanca (Anuario ThinkEPI, 2022)
We present the results of the Harbinger project, carried out between 2016 and 2022 in several countries on three continents, which focused on the use that early career researchers make of the resources available through university libraries. These include catalogs, databases, and big deals, as well as alternative platforms such as Google search engines, academic social networks (ResearchGate), and pirate platforms (Sci-Hub). Likewise, the project inquires as to the holdings of institutional repositories and the future that these researchers predict for academic libraries. It concludes with the need for libraries to strengthen communication and support for researchers, taking into account in particular the early career researchers who are the future of science.
Keywords: 2016-2022; Academic libraries' future; Attitudes; Competitors; Early career researchers; Harbingers projects; Institutional repositories; Practices; Shadow libraries; University libraries